A respectful design approach to facilitate codesign with people with cognitive or sensory impairments and makers. Issue 2 (3rd April 2021) - Rajapakse, Ravihansa; Brereton, Margot; Sitbon, Laurianne
ABSTRACT: People with cognitive or sensory impairments (CSI) often have abilities, needs and desires that are not catered for by conventional service provision. This presents opportunities for volunteer makers to help co-create alternative futures with them. We describe a codesign process with people with CSI, their caregivers and family members, design researchers and makers. First, we focus on recruitment of design clients with CSI and the volunteer designer-makers, as recruitment is often overlooked in reporting. We explore ways of matching makers and their skills with design clients. We used codesign methods with our participants that suited their communication abilities and interests. Design props supported them to express and communicate their needs to design researchers, while limiting disclosure of personal information. Our findings indicate that codesign work with people with CSI involves (1) negotiating access, (2) mutual learning to create shared understanding and trust, (3) developing communication and participation through valuing unique abilities and interests, and (4) using design props to engage makers. We contribute an approach of respectful design, which emphasises mutual learning, self-expression and self-determination for people with CSI. This approach supports people with CSI to express themselves and assists their communication with potential volunteer makers and service providers.